Modification of the existing maximum residue level for aclonifen in anise/aniseed - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Luis Carrasco Cabrera; Irene Castellan; Monica delAguila; Lucien Ferreira; Luna Greco; Samira Jarrah; Renata Leuschner; Andrea Mioč; Stefanie Nave; et al. (EFSA Journal, 2025)
Abstract In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Landesanstalt für Landwirtschaft und Gartenbau submitted a request to the competent national authority in Germany to modify the existing maximum residue level (MRL) for the active substance aclonifen in anise/aniseed. The data submitted in support of the request were found to be sufficient to derive an MRL proposal for the crop of interest. Adequate analytical methods for enforcement are available to control the residues of aclonifen in the plant matrix under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of aclonifen according to the reported agricultural practice is unlikely to present a risk to consumer health.